Consideration of anthropogenic factors in boreal forest fire regime changes during rapid socio-economic development: case study of forestry districts with increasing burnt area in the Sakha Republic, Russia. (6th March 2020) - Kirillina, Kiunnei; Shvetsov, Evgeny G; Protopopova, Viktoriya V; Thiesmeyer, Lynn; Yan, Wanglin
Abstract: This paper presents an original approach to characterizing historical fire regimes for regions with limited fire data. Fire variables were derived from satellite datasets and regional fire occurrence statistics. They defined the integral elements of a fire regime such as historical trends, spatiotemporal evolution, fire seasonality and causes. Temporal evolution was investigated based on a regime shift detection method developed by Rodionov while changes in the fire regime were analyzed for statistical significance using the Mann–Kendall trend test and Sen's slope estimator. A descriptive analysis was performed to assess fire seasonality, causes, and together formed the basis for this methodology. We validated the proposed approach by assessing historical fire activity in the Sakha Republic (Yakutia), which is one of the most fire-prone regions of Russia. The assessment was conducted with data from the period of 1996–2018. We detected increases in historical fire activity as well as thresholds of change in the fire regime. Changes during the analysis period included lengthening of fire season, increased burned area extent, and extension of peak fire period. Overall, significant changes in the fire regime were detected in the regions strongly affected by warming and increasing anthropogenic alteration.